Systematic identification of Ctr9 regulome in ERα-positive breast cancer. (December 2016) - Zeng, Hao; Lu, Li; Chan, Ngai; Horswill, Mark; Ahlquist, Paul; Zhong, Xuehua; Xu, Wei
Abstract Background We had previously identified Ctr9, the key scaffold subunit of the human RNA polymerase II (RNAPII) associated factor complex (PAFc), as a key factor regulating a massive ERα target gene expression and ERα-positive breast cancer growth. Furthermore, we have shown that knockdown of Ctr9 reduces ERα protein stability and decreases the occupancy of ERα and RNAPII at a few ERα-target loci. However, it remains to be determined whether Ctr9 controls ERα-target gene expression by regulating the global chromatin occupancy of ERα and RNAPII in the presence of estrogen. Results In this study, we determined the genome-wide ERα and RNAPII occupancy in response to estrogen treatment and/or Ctr9 knockdown by performing chromatin immunoprecipitation coupled with high-throughput sequencing (ChIP-seq). We found that loss of Ctr9 dramatically decreases the global occupancy of ERα and RNAPII, highlighting the significance of Ctr9 in regulating estrogen signaling in ERα-positive breast cancer cells. Combining this resource with previously published genomic data sets, we identified a unique subset of ERα and Ctr9 target genes, and further delineated the independent function of Ctr9 from other subunits in PAFc when regulating transcription. Conclusions Our data demonstrated that Ctr9, independent of other PAFc subunits, controls ERα-target gene expression by regulating global chromatin occupancies of ERα and RNAPII.